Community Awareness of HPV Screening and Vaccination in Odisha - Niharika Khanna; Aparna Ramaseshan; Stephanie Arnold; Kalpana Panigrahi; Mark D. Macek; Bijaya K. Padhi; Diptirani Samanta; Surendra N. Senapati; Pinaki Panigrahi (Obstetrics and Gynecology International)
Introduction. A number of new technologies including cervical cancer screening and vaccination have introduced new tools in the fight against cervical cancer. Methods. This study was set in Odisha, India, at the Acharya Harihar Regional Cancer Center and study research infrastructure at the Asian Institute of Public Health. IRB approvals were obtained and a research assistant recruited 286 women aged 18–49 years, who provided informed consent and completed a survey tool. Data were entered into EpiData software and statistical analysis was conducted. Results. 76.3% women participants were married, 45.5% had sexual debut at age 21 or greater, 60.5% used contraception, 12.2% reported having a Pap smear in the past, and 4.9% reported having prior genital warts. Most, 68.8% had never heard of HPV and 11.9% were aware that HPV is the main cause of cervical cancer. 82.9% women thought that vaccinations prevent disease, and 74.8% said they make the decision to vaccinate their children. Conclusion. The Odisha community demonstrated a low level of knowledge about cervical cancer prevention, accepted vaccinations in the prevention of disease and screening, and identified mothers/guardians as the key family contacts.